Pengertian dan Syarat Mujtahid dalam Ilmu Fikih dan Perkembangannya Diri Masa Kemasa - Abdul Latif Khan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This article discusses the concept of mujtahid or fakih in Islamic jurisprudence, the requirements that must be met by a mujtahid, and the development of ijtihad from time to time. In addition, this article also explains several famous mujtahid figures in Islamic history and their roles in the formation of sharia laws.